2018
DOI: 10.1080/07391102.2018.1438923
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulation of metal free structure of Lmb, a laminin-binding adhesin of Streptococcus agalactiae: metal removal and its structural implications

Abstract: Metal-binding receptors are one of the extracellular components of ATP-binding cassette transporters that are essential for regulation of metal homeostasis in bacteria. Laminin-binding adhesin (Lmb) of Streptococcus agalactiae falls under this class of solute binding proteins. It binds to zinc with a high affinity. Crystal structure of Lmb solved previously by our group reveals that the zinc is tetrahedrally coordinated by three histidines and a glutamate at the interdomain cleft. Lmb contains a long disordere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…In this study, PCR showed that the cfb, cylE, fbsA, fbsB, hylB, and enolase virulence genes were present in all isolates, whereas the bac and lmb genes were not; the detection rates were the same with those reported for isolates in Argentina [67]. These virulence factors provide essential assistance for allowing pathogenic bacteria to invade the host and to be directly involved in the invasion process [68]. Notably, cylE is a pore-forming toxin involved in tissue damage and systemic dissemination of bacteria [69].…”
Section: Plos Onesupporting
confidence: 73%
“…In this study, PCR showed that the cfb, cylE, fbsA, fbsB, hylB, and enolase virulence genes were present in all isolates, whereas the bac and lmb genes were not; the detection rates were the same with those reported for isolates in Argentina [67]. These virulence factors provide essential assistance for allowing pathogenic bacteria to invade the host and to be directly involved in the invasion process [68]. Notably, cylE is a pore-forming toxin involved in tissue damage and systemic dissemination of bacteria [69].…”
Section: Plos Onesupporting
confidence: 73%
“…Unlike AztC, the apo form of TroA does not show any significant displacement of the Z-Loop relative to the holo form [ 40 ]. Although no apo structure exists for Lmb or Lbp, a recent molecular dynamics simulation of both Lmb and TroA indicated significant flexibility of the Z-Loop in the apo form and displacement away from the zinc binding site upon zinc loss [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The flexible loop, typical of zinc-specific binding proteins, is present but does not contain the His-rich motif [ 75 ]. Their mechanism of metal binding and release has been only hypothesised by means of molecular dynamics simulation [ 76 ]. Despite the structural similarities and the genetic homology with Spn AdcAII, the laminin-binding ability has not been confirmed in the case of Spn AdcAII and the analysis of the surface charge distribution between Sag Lmb and Spn AdcAII revealed significant differences, attributable to the “extra” adhesion functionality [ 52 , 77 ].…”
Section: Abc Transporter Related Zincophores: Zinc-substrate Binding ...mentioning
confidence: 99%